PENGGUNAAN TEKNIK DIVERSI DALAM PROSES PERADILAN PIDANA ANAK - Warumboy, Charolin Khristy; Mardian Putra Frans (The Juris, 2024)
This research aims to annotate the application of diversion in Decision Number 7/Pid/ Sus.Anak/2019/PN Jap. In this decision, the child was sentenced to imprisonment for 4 (four) months, while the Public Prosecutor (JPU) as law enforcer was obliged to carry out diversion. "How diversion efforts should have been carried out but the facts of the decision did not appear." So it is necessary to carry out legal research as to why the decision did not use diversion first. The enactment of Law No. 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law) marks a significant step towards providing special protection for children in conflict with the law. In this research, the focus lies on children in conflict with the law. The primary aim of this law is to enhance the regulation of the juvenile criminal justice system, ensuring better treatment and outcomes for children involved in legal conflicts. Legal protection for children is needed so that children receive attention from errors in the application of statutory regulations, which cause physical, mental and social harm. The aim of this research is to discover, describe (describe), and analyze the application of the diversion method in resolving criminal cases by children studying decision number 7/pid/sus.anak/2019/pn jap.